5-3(x+3)=-11x-36

Simple and best practice solution for 5-3(x+3)=-11x-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(x+3)=-11x-36 equation:



5-3(x+3)=-11x-36
We move all terms to the left:
5-3(x+3)-(-11x-36)=0
We multiply parentheses
-3x-(-11x-36)-9+5=0
We get rid of parentheses
-3x+11x+36-9+5=0
We add all the numbers together, and all the variables
8x+32=0
We move all terms containing x to the left, all other terms to the right
8x=-32
x=-32/8
x=-4

See similar equations:

| 20−x=7 | | 25=5-10w | | 2x-6-10x=20 | | s/2.8=5.9 | | X-5=0.1(x | | -22=-7h+20 | | 1-x=6x+8 | | 26+3x=-13 | | 2/3r+15=17 | | -20=3x-7+x | | -4+k/4=-6 | | 12-6k=2(6-3k) | | q/(-2)=8 | | 0.4r−1.2=0.3r+0.6 | | 2/5n+1/10=1/2n+3 | | 14x2x+12=12x2x+5 | | 1.4=28/x | | 22=-8u+6(u+4) | | 7w=-11 | | 19+x=17-5x | | 2p-8/p+3=8/10 | | -279=-9x | | 8.16-0.2n=-13.8n | | 2(1/2x+6)=3(x+-3) | | 21=-3x+15 | | -8-4x=-2x+22 | | 8z-4(z+8)=8 | | 4y−6=y−6 | | y=1000(1.4^4) | | 1q+2=6 | | (w)/(-2.5)=8 | | 1/24=-8/9k |

Equations solver categories